Nutritional Value of Palm Meristem from Phoenix dactylifera L. and Its Effect on Polycystic Ovary Syndrome in Female Rats Induced with Estradiol Valerate - Ghofran Hadi Mashkour Sangar; Naser Mirazi; Nasim Hayati Roodbari; Abdolkarim Hossieni (World Journal of Traditional Chinese Medicine)
Objective: Polycystic ovary syndrome (PCOS) is the most prevalent endocrine disorder in women of reproductive age. The objective of our investigation is to study the protective effect of hydroethanolic extract of palm meristem (HEPM) on female rats with PCOS. Materials and Methods: The experimental study involved the placement of 42 adult female Wistar rats (n = 7) into six groups, with the control group receiving 0.25 ml of physiological serum by gavage daily, the sham group getting 0.25 ml of olive oil, and the HEPM 250, 500, and 500 per se group taking HEPM by gavage daily. PCOS was induced with estradiol valerate (EV), which was administered through a subcutaneous injection at 2 mg/kg volume using 0.25 ml of olive oil. After experiments, all animals were subjected to anesthesia, and serums were extracted for biochemical and hormonal evaluation. Results: EV showed marked increases in serum levels of testosterone and luteinizing hormone when compared with the control group. Significantly, the EV group decreased 17-β estradiol, progesterone, and follicle-stimulating hormone. There was a significant alteration in hormonal levels across the treatment groups. The serum malondialdehyde levels and total oxidant status were elevated in the EV group. In addition, the serum levels of total antioxidant capacity, glutathione, and glutathione peroxidase were significantly lower in the EV group than in control rats. In the treatment groups, HEPM significantly reverses the oxidant/antioxidant balance and ameliorates the adverse effect of PCOS on oxidative stress. Conclusion: The study findings indicated that the HEPM effectively safeguarded ovarian tissue from developing PCOS in the presence of EV.